2018
DOI: 10.1017/s0266462318000314
|View full text |Cite
|
Sign up to set email alerts
|

Health Technology Assessment Methods Guidelines for Medical Devices: How Can We Address the Gaps? The International Federation of Medical and Biological Engineering Perspective

Abstract: (2018) Health technology assessment methods guidelines for medical devices : how can we address the gaps? The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 22 publications
0
26
0
1
Order By: Relevance
“…As opposed to pharmaceuticals, medical devices have a greater potential to indirectly impact an organization. Improvements, especially from an economic standpoint, can be gained by optimizing patient pathways or hospital workflows (26, 33, 34). Due to the learning curve, there may also be need for staff training, or the requirement for a sterilization process to be put in place for a reusable device.…”
Section: Issues Specific To Medical Devices Are Mainly Unresolved In mentioning
confidence: 99%
“…As opposed to pharmaceuticals, medical devices have a greater potential to indirectly impact an organization. Improvements, especially from an economic standpoint, can be gained by optimizing patient pathways or hospital workflows (26, 33, 34). Due to the learning curve, there may also be need for staff training, or the requirement for a sterilization process to be put in place for a reusable device.…”
Section: Issues Specific To Medical Devices Are Mainly Unresolved In mentioning
confidence: 99%
“…For the latter, moving towards the paradigm of precision medicine can be even more critical. Medical devices effectiveness is dependent upon several factors including the environment in which are utilised (e.g., sterilised or not, temperature, humidity, dust), the experience of the operators, maintaining, servicing and preparing the medical device 9 . For instance, recent studies demonstrated that even the positioning of applied parts (e.g., probes, sensors) in a trial might affect the significance of the results 10 .…”
mentioning
confidence: 99%
“…For this, the information is structured according to the following fields: names of the authors, title of the article, methodologies (HTA or mini-HTA or any other unspecified methodology), multi-criteria techniques and main assessment criteria (health problems and use of technology, description and technical characteristics, safety, clinical effectiveness, costs and economic evaluation, ethical analysis, organizational / institutional aspects and human resources, patient and social aspects, legal aspects, among others). In addition, 14 guidelines and methodologies proposed by international HTA agencies were reviewed, allowing the conceptualization of methodologies used internationally [11,12,16,23,24,30,31,[33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Methodsmentioning
confidence: 99%